Protocolo de avaliação rápida para o monitoramento de nascentes em Vereda - Guimarães, Ariane (2016)
This study aimed to adapt a rapid assessment protocol for Vereda environments that are inserted in the Cerrado biome. For this was taken as a "reference condition" conditions found in the Alto area course the basin of Ribeirão Vai-e-Vem in Ipameri (GO). Considering the dynamics of the protocol, the following parameters were proposed: Buriti Presence Extension conservation area around Vereda, Isolation nascente- protection structure, spring surrounding vegetation in Vereda, State of vegetation conservation around the spring in Vereda, pollution in the environment and in flooded area of Vereda spring, plant and buildings at the source in Vereda.For each parameter it was atributted a corresponding value according to the environmental stress gradient verified in the assessment location, may vary from a "bad" situation (score from 0 to 5), a "set" situation (5.1 to 10), a "good’ situation (10.1 to 15) up to an "excelente” situation (15.1 to 20). The work also describes the use of geoprocessing techniques to conduct a qualitative and quantitative analysis of the source areas (of the upper course of the watershed of Vai-e-Vem River) and ascertain the main environmental impacts in these areas, from the use and land occupation. For processing data were used GIS tools. About the use of land in the area of the upper course of Vai-e-Vem River in the year 2015, it was found that 48.57% of the area corresponds to areas of agriculture, 17.37% are pasture areas and 20.61 % are remaining of primary phytophysiognomies To conclude, this study provides a rapid assessment protocol that can be applied in the monitoring of sources at Veredas and demonstrates the importance of tool’s utilization in the GIS environment and satellite images applied in scientific research, notedly for environmental studies and detection of impacts.